The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/b94477
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport in DNA-Based Devices

Abstract: Charge migration along DNA molecules has attracted scientific interest for over half a century.Reports on possible high rates of charge transfer between donor and acceptor through the DNA, obtained in the last decade from solution chemistry experiments on large numbers of molecules, triggered a series of direct electrical transport measurements through DNA single molecules, bundles and networks. These measurements are reviewed and presented here. From these experiments we conclude that electrical transport is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
191
0
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(210 citation statements)
references
References 142 publications
3
191
0
13
Order By: Relevance
“…Representative results on the applications of nanogap electrodes in nano-and single molecular devices have been summarized by several authoritative reviews. [164][165][166][167][168][169][170][171][172][173] Limited by the capacity of the present paper, we do not plan to overlap these reviewed topics, and only focus on the possibility of combining conjugated polymers with nanogap electrodes, in order to introduce the properties associated with conjugated polymers into such nanodevices. Based on our recent experience, [156,[174][175][176][177] we will exemplify this combination using a Since the discovery of conductive polymers in the 1970s, thousands of conjugated polymers have been synthesized and investigated, and some have been successfully applied in polymer electronics since the 1990s.…”
Section: Applicationsmentioning
confidence: 99%
“…Representative results on the applications of nanogap electrodes in nano-and single molecular devices have been summarized by several authoritative reviews. [164][165][166][167][168][169][170][171][172][173] Limited by the capacity of the present paper, we do not plan to overlap these reviewed topics, and only focus on the possibility of combining conjugated polymers with nanogap electrodes, in order to introduce the properties associated with conjugated polymers into such nanodevices. Based on our recent experience, [156,[174][175][176][177] we will exemplify this combination using a Since the discovery of conductive polymers in the 1970s, thousands of conjugated polymers have been synthesized and investigated, and some have been successfully applied in polymer electronics since the 1990s.…”
Section: Applicationsmentioning
confidence: 99%
“…Delocalized coherent transport is dismissed in biomolecules due to their lack of periodicity, random fluctuations, and limited conductance values from experiments. Even for a poly-guanine structure (prime candidate for a conduction pathway building block, owing to its relatively low ionization potential), simulations have shown that their stacking in the DNA duplex should not yield any extended states, or that the band gap is very large (For a thorough review of earlier attempts at explaining charge transport, see [3] and the references therein). In contrast to the familiar phonon-assisted hopping of solid-state physics, Schlag et al [39] proposed a "rest and fire" model for charge hopping along a loose peptide backbone, implemented using classical molecular dynamics simulations and chemical kinetics theory of electron transfer.…”
Section: Conductance Theories For Biomoleculesmentioning
confidence: 99%
“…Usually, tight-binding Hamiltonians are employed to describe electronic structures of DNA duplexes -both explicitly (in the form of the "fishbone", "ladder" and similar models -see, for example, [51,53,58,60,[64][65][66][67][68][69][70][71][72] and the pertinent review articles [3,[73][74][75][76][77] ) and implicitly (within the framework of Marcus-type theories of charge transfer, for example, [55,[78][79][80][81] and the references therein). These works were successful in qualitatively (and sometimes even quantitatively) describing numerous experimental data (see, for example, [42,56,57,82,83] and the references therein) on transfer of injected single holes (or injected single electrons) through DNA duplexes.…”
Section: Critical Assessment Of the Biopolymer Charge Transfer/transpmentioning
confidence: 99%
“…As a consequence, the identification of the relevant charge transport channels in DNA systems becomes a crucial issue. Transport experiments in DNA derivatives are however quite controversial [4,5]. DNA has been characterized as insulating [6], semiconducting [7] or metallic [8,9].…”
mentioning
confidence: 99%